2009
DOI: 10.1200/jco.2008.21.4882
|View full text |Cite
|
Sign up to set email alerts
|

Targeted High-Resolution Ultrasound Is Not an Effective Substitute for Sentinel Lymph Node Biopsy in Patients With Primary Cutaneous Melanoma

Abstract: US is not an appropriate substitute for SLN biopsy, but it is of value in preoperative SLN assessment and postoperative monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 21 publications
0
63
0
2
Order By: Relevance
“…As suggested by various clinical and preclinical studies (14,19), we used architectural criteria on ultrasound images together with changes in nodal volume to predict the presence of metastases in PLNs. Although PLN status was successfully predicted by these methods in 47 of the 49 mice studied, 1 PLN was judged as false-negative and 1 as false-positive by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested by various clinical and preclinical studies (14,19), we used architectural criteria on ultrasound images together with changes in nodal volume to predict the presence of metastases in PLNs. Although PLN status was successfully predicted by these methods in 47 of the 49 mice studied, 1 PLN was judged as false-negative and 1 as false-positive by ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…At 5 d after tumor implantation, ultrasound scans revealed that 10 of the 49 mice had an increased left PLN volume, in many cases associated with irregular, crenulated edges suggestive of nodal metastasis (14,19). Typical day 5 ultrasound images for negative and positive PLNs are shown in Figure 1A.…”
Section: Identification Of Pln Metastasis By 3-dimensional Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…A few radiologists are in favor of staging regional lymph node basins in stage I-II melanoma with high-resolution ultrasonography [24][25][26]. However, the general opinion is that targeted high-resolution ultrasonography is not an effective substitute for SLNB in patients with primary melanoma [27][28][29][30]. Several authors investigated the use of chest x-rays in staging and concluded that its use is questionable, because of low detection rates, high false-positive percentages and subsequent high patient anxiety [31][32][33].…”
Section: Reviewmentioning
confidence: 99%
“…In the case of a positive SLN a radical lymphadenectomy could be performed directly without scheduling a second surgery at a later date. Methods such as high resolution ultrasound imaging 6 and frozen section histopathological examination 7 have been evaluated as intraoperative techniques to lead to one-step surgery. However, these methods have not achieved the required sensitivities, with false negative rates up to 10%.…”
mentioning
confidence: 99%